Displacement Effects in Manufacturing and Structural Change - Ines Helm; Alice Kügler; Uta Schönberg (Institute of Labor Economics (IZA), 2023)
We investigate the consequences of structural change for workers displaced from the manufacturing sector. Manufacturing establishments traditionally employed low- and high-wage workers in similar proportions and paid substantial wage premiums to both types of workers. Structural change has led to the disappearance of these jobs, particularly for low-wage workers. Decomposing displacement wage losses, we show that low-wage workers suffer considerable losses in establishment premiums following displacement, whereas high-wage workers tend to fall down the match quality ladder. With ongoing structural change, losses in wages and establishment premiums have increased over time, especially for low-wage workers, in part because they are increasingly forced to switch to low-knowledge service jobs where establishment premiums are low. Our findings further highlight that structural change and layoffs in manufacturing have significantly contributed to job polarization and the rise in assortative matching of workers to firms.
Keywords: J22; J24; J31; J63; 330; structural change; manufacturing decline; displaced workers; cost of job loss; human capital; firm rents